Commentaries on “Informatics and Medicine: From Molecules to Populations” - Altman, R. B.; Balling, R.; Brinkley, J. F.; Coiera, E.; Consorti, F.; Dhansay, M. A.; Geissbuhler, A.; Hersh, W.; Kwankam, S. Y.; Lorenzi, N. M.; Martin-Sanchez, F.; Mihalas, G. I.; Shahar, Y.; Takabayashi, K.; Wiederhold, G. (Methods of Information in Medicine, 2008)
Objective: To discuss interdisciplinary research and education in the context of informatics and medicine by commenting on the paper of Kuhn et al. “Informatics and Medicine: From Molecules to Populations”.Method: Inviting an international group of experts in biomedical and health informatics and related disciplines to comment on this paper.Results and Conclusions: The commentaries include a wide range of reasoned arguments and original position statements which, while strongly endorsing the educational needs identified by Kuhn et al., also point out fundamental challenges that are very specific to the unusual combination of scientific, technological, personal and social problems characterizing biomedical informatics. They point to the ultimate objectives of managing difficult human health problems, which are unlikely to yield to technological solutions alone. The psychological, societal, and environmental components of health and disease are emphasized by several of the commentators, setting the stage for further debate and constructive suggestions.
Keywords: Medical informatics; biomedical informatics; health informatics; interdisciplinarity